The Influence of Employee Engagement, Psychological Capital, and Work-life Balance on Turnover Intention through the mediation of Job Satisfaction of Private Employees in Jabodetabek - Tegar Anugrah (Journal of Applied Business Administration, 2025)
This study aims to analyze the influence of employee engagement, psychological capital, and work-life balance on turnover intention with job satisfaction as a mediating variable. In this study, a quantitative approach was used on 439 private employees in Greater Jakarta. This approach uses the Partial Least Squares–Structural Equation Modelling (PLS-SEM) analysis technique. Research shows that employee engagement, psychological capital, and work-life balance have a significant positive effect on  employee job satisfaction. In addition, it is proven that job satisfaction has a significant negative effect on turnover intention. All three independent variables have a significant effect on turnover intention, either directly or indirectly through job satisfaction as a mediator. Employee engagement is reported to be the most significant factor in increasing job satisfaction and reducing the desire to leave work. These results support the theory of Job Demands-Resources and Social Exchange Theory, both of which emphasize the importance of psychological resources and social relationships in work. In addition, this study also found that there were differences in views between generations about the variables discussed. This research provides theoretical contributions and practical benefits to the development of sustainable employee retention strategies.